Ecotoxicology of heavy metals (Cd, Pb, Zn and Cu) in flat tree oysters Isognomon alatus (GMELIN) from Sepang, Malaysia - Saed, Katayon (2001)
The status of heavy metals pollution in the Sepang Besar River and Sepang Kecil River was studied in August 1998. In general heavy metals concentrations in flat tree oyster 1. alatus, sediments and water from Sepang Besar River were found significantly (p <0.05) higher than those from Sepang Kecil River. Furthermore field experiments were conducted to study the accumulation and depuration of heavy metals in oysters. The rates of metals accumulations in oysters were found to be 42.70, 1.77, 0.95, 0.84 µg g⁻¹ month⁻¹ for Zn, Cu, Cd and Pb, respectively. The polluted oysters were transferred to clean area to estimate the depuration rates. Significant reduction of metals concentrations in oyster was observed. About 87%, 83%, 78% and 59% for Cd, Pb, Cu and Zn were detected after six months being transferred to clean area, respectively. The metals accumulation and depurations patterns in oysters in the laboratory conditions were also investigated. The mean metal concentrations in oysters exposed to metals solution of 100 µg rt at the end of two weeks were 32.70, 63. 19, 35.40, 7.44 µg got , which were 44, 3, 8 and 7 times greater than their initial levels for Cd, Zn, Cu and Pb, respectively. The exposed oysters were transferred to clean seawater and the metals depurations were investigated for one week. In general about 78%, 81%, 87% and 88% of the accumulated Zn, Cu, Pb and Cd were depurated from oysters 1. alatus. Results from laboratory experiments indicated that there were differences in the mechanisms for the metals accumulation and depurations in various organs of 1. alatus. In general, in both accumulation and depuration experiments, gill, byssus and mantle play major role whereas muscle, shell and visceral mass have no significant role. Furthermore laboratory experiments were showed that the accumulation rates of metals through contaminated water were higher than the metals accumulation rates through contaminated algae. It is believed that oysters 1. alatus accumulate heavy metals through contaminated seawater rather than contaminated algae. The LCso levels of metals for oysters were observed to be 478.63, 436.51, 676.08 and 295.12 µg rl for Cu, Pb, Zn and Cd, respectively. The toxicity effects of heavy metals on filtration rate of oysters were also studied and the filtration rate of oysters 1. alatus exposed to 125 and 150 µg rl of all metals were decreased. In both toxicity experiments the trend of metals toxicity on oysters were found Cd > Pb > Cu > Zn.